Saturday

April 19, 2014

April 19, 2014

Posted by **Jeconiah** on Tuesday, March 26, 2013 at 11:47pm.

- Math -
**Steve**, Wednesday, March 27, 2013 at 10:58amlog(x-2) + log(x-4)/log8 = log(x-1)/log6

log[(x-2)(x-4)^(1/log8)] = log[(x-1)^(1/log6)]

(x-2)(x-4)^(1/log8) = (x-1)^(1/log6)

Ya got me.

Something tells me the problem was not as posted.

- Math -
**Cedric**, Thursday, March 28, 2013 at 5:45amplease solve it

**Related Questions**

Math - The problem I have to solve is log with base 2 ^6 multiply by log base 6...

math 12 - log6=x and log8=y, determine an expression for log3 in terms of x an y...

Algebra 1 - solve: log8(w-6)=2-log8(w+15) note: the 8 is to be little at the ...

Test prep - solve: log8(w-6)=2-log8(w+15) note: the 8 is to be little at the ...

Please help me!!!! maths - Solve for x: log5(x-2)+log8(x-4) = log6(x-1). I do ...

math - (6) Which equation is equivalent to 4^-x=8? a. log8 4=x b. logx = -4 c. ...

math log - if log6=m and log 5=n, write 7.2 as an expression in m and n Answer ...

precalulus - Ok feeling kinda dumb because this isn't coming out right. I know ...

Algebra - How do I start to solve -2log8(x+1) = -8? I think -2log8(x+1) is log8...

Math - Which of the following is equal to log6(t + 1) − log6(t^2 − 1...